Health Service Delivery and Challenges Encountered in Public Hospitals in the Second District of Laguna: Basis for an Action Plan - David, Kimberly Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the level of health service delivery and the challenges encountered by patients in public hospitals in the Second District of Laguna as basis for an action plan. It assessed health service delivery in terms of patient admission, medical service, supportive service, hospital discharge process, and hospital social responsibility, and examined patient challenges in terms of perceived susceptibility, perceived severity, perceived benefits, and perceived barriers. The study used a quantitative descriptive-correlational research design with 375 patient-respondents from Ospital ng Cabuyao, Cabuyao City Hospital, and Pagamutang Pangmasa ng Laguna–Maitim, Bay. Data were gathered through a researcher-made survey questionnaire and analyzed using weighted mean, standard deviation, and Pearson Product-Moment Correlation. Findings showed that health service delivery was generally rated good, while the challenges encountered by patients were rated serious to very serious. A significant relationship was found between selected dimensions of health service delivery and the seriousness of patient challenges. Based on the findings, an action plan was proposed to improve hospital services, address patient concerns, and enhance patient-centered care in public hospitals in the Second District of Laguna.
Keywords: Health Service Delivery, Public Hospitals, Patient Satisfaction, Patient Challenges, Health Service Quality, Descriptive-Correlational Study, Laguna, Action Plan